Estimation of Blue Carbon Ecosystem Potential in The Mangrove Forest Tourism Area of Langsa Protected Zone - Lola Adres Yanti; Astri Winda Siregar; Mona Fhitri Srena; Fikrinda; Ariz Umar Ramadhan; Afrizal Murdi; Febrian Supriadi Laba Pardamean Berutu; Mizan Jrohna; Ilham Hanafi; Aang Kunaifi; Dedy Fitriandi (Talenta Publisher, 2026)
Mangrove forests are vital coastal ecosystems that sequester large amounts of carbon, helping mitigate climate change. Indonesia has the world’s largest mangrove area, including the Langsa Protected Mangrove Forest in Aceh, which holds high biodiversity and significant blue carbon potential. The Mangrove Forest Tourism Area in Langsa is one of the largest in Southeast Asia; therefore, estimating its carbon potential is essential to support Indonesia’s commitments to the Paris Agreement and carbon trading initiatives. This study aims to (1) identify tree species diversity in mangrove, and (2) estimate aboveground biomass, carbon stock, and carbon sequestration in the Langsa Mangrove Forest Tourism Area. A purposive sampling method was used for the initial plot, followed by systematic sampling. From 369.01 hectares of mangrove area, 19 plots were established with sizes of 10 m × 10 m for trees, 5 m × 5 m for saplings, and 2 m x 2 m for seedlings. Carbon stock estimation employed species-specific allometric equations. Out of 293 individual trees, four tree species, namely Rhizophora mucronata, Rhizophora apiculata, Bruguiera gymnorrhiza, and Ceriops tagal, were identified, with most ranging within 3.18–4.61 cm diameter classes. The highest aboveground biomass, carbon stock, and carbon sequestration were found in plot 19, at 27.66 ±13.18 tons/ha), 13.00 ±6.20 tons C/ha), and 47.67 ±22.71 tons CO₂/ha), respectively. These findings highlight the substantial blue carbon potential of the Langsa Mangrove Forest in a protected area, emphasizing its importance in regional conservation strategies.